2019
DOI: 10.5114/aic.2019.90220
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observation of adults after successful repair of aortic coarctation

Abstract: Introduction: Despite successful repair of aortic coarctation, cardiovascular complications occur. Aim: To analyse type and frequency of late complications and their impact on exercise capacity in adults after aortic coarctation repair. Material and methods: Fifty-eight adults after aortic coarctation repair, 36 male, median age 27.46 ±10.57, were compared to 30 healthy volunteers. Physical examination, transthoracic echocardiography, carotid intima-media thickness measurement, cardiopulmonary exercise test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The remaining full texts were requested via our library, but only 4 published in English were used. After consulting the full content of these 356 articles, only 17 fulfilled the inclusion criteria as set out above (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The remaining full texts were requested via our library, but only 4 published in English were used. After consulting the full content of these 356 articles, only 17 fulfilled the inclusion criteria as set out above (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Table 1).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In the past 2 decades, studies on neonates with repaired coarctation measuring aortic wall stiffness and distensibility found impaired elastic properties of the ascending aorta, supporting the assumption that coarctation was not only a localized aortic isthmus abnormality but also a systemic vascular disease of the precoarctation aorta. 10 , 11 Although some earlier studies found the incidence of hypertension was higher in late coarctation repair, 12 recent studies show a strong association between coarctation and risk of hypertension and coronary artery disease 13 and that elastic properties of the ascending aorta were abnormal even in newborns who underwent early repair, suggesting that this increased risk was related to the abnormal prestenotic aortic vascular bed. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, these trials do not provide data regarding how exercise capacity is related to relative severity of coarctation, whether anatomical or CoA gradient-based. Rog et al 16 compared patients with prior CoA repair to healthy controls using echocardiography and CPET and found that patients with prior CoA repair had significantly greater peak gradient of the coarctation and significantly lower exercise capacity, but did not find any associations between echocardiographic and CPET parameters. Similarly, 2 studies by Trojnarska et al 17 , 18 demonstrated that patients with prior surgically repaired CoA with recurrent coarctation had similar exercise tolerance to controls and that exercise capacity did not relate to whether patients had severe or nonsevere recoarctation, with severity defined by a mean coarctation gradient at rest >25 mm Hg by echocardiography.…”
Section: Discussionmentioning
confidence: 99%